Marginalized Voices in Iraqi Fiction: A textual reading of Inaam Kachachi's The Dispersal - Mohammed, Estabraq Yahya; Vafa, Amirhossein (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2024)
The current paper discusses the representation of Iraqi female narratives and the experience of Wardiyah in Kachachi's The Dispersal. It shows how Iraqi women's fiction uses writing techniques to express political conflicts. It examines the challenges faced by Wardiyah in her pursuit of a medical career in the fifties of the twentieth century in the context of Iraq and later her migration to France. The paper stresses the global reach and the political expression of women's literature in Iraq, which has previously been neglected or interrupted in alternative geopolitical contexts by applying a textual reading. It highlights the daily lives and struggles of marginalized groups like Christians and women, addressing cultural, faith, social class environment, and women's rights. The textual analysis is based on the novel The Dispersal by Inaam Kachachi, which follows the life of Wardiyah, a gynaecologist, and her experiences in different eras of Iraqi history. The approach was thematically designed, with a focus on core areas that impact the narrative, including discussions of healthcare and women's experiences. The paper discusses how the main character represents the defective healthcare system and cultural values that lead to the deterring of women from receiving medical attention in 1950s Iraq. Some passages are discussed illustrating how such challenges related to people's perception of women's health concerns impinged on Wardiyah's professional life This study examines the impact of sociocultural factors on the lives and careers of women in the healthcare sector. It draws on a case study of Wardiyah, a woman who has faced challenges related to her gender and cultural background in her professional practice. It also looks at the experiences of Hinda, another woman in the healthcare sector. Hinda has experienced challenges in adapting to a new cultural environment and in achieving recognition within her professional field.